PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI TERHADAP TINDAK PIDANA CYBER CRIME PHISING DI INDONESIA - AZ, Mutiara; Samawati, Putu (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The development of the internet has enabled the unlimited exchange of information, but it has also given rise to new forms of crime such as phishing. This study uses a normative legal method to analyse phishing as a cybercrime that utilises email, social media, and malicious software to obtain personal or financial data illegally. Technological advances have expanded the modes of phishing and increased its vulnerability. Countermeasures are carried out through relevant provisions of the Criminal Code, such as Article 362 on Theft, Article 378 on Fraud, and Article 263 on Identity Fraud. More specific regulations are contained in Law No. 11 of 2008 in conjunction with Law No. 19 of 2016 on ITE, particularly Articles 27–37 concerning prohibited acts and Articles 45–52 concerning criminal sanctions, with the threat of imprisonment for up to twelve years and a maximum fine of Rp2 billion